Are Customers Happy? A Study of Satisfaction in Sarawak’s Fast-Food Restaurants - Nancy Thien Swee Yen; Malisah Latip (Universiti Sains Islam Malaysia, 2025)
Sains Insani, Volume 9 Issue 2 Page (440-454)